(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
The study was conducted for the assessment of marketing system of summer tomato in Jashore. Summer tomato had high demand and high value crop in summer season among the consumers. Data were collected from 30 randomly selected tomato farmers and 60 traders from different market of Jashore district of Bangladesh during July-October, 2019. Farmer, faria, bepari, wholesaler, commission agents and retailer were involved in marketing of summer tomato. Marketing cost of farmar, faria, bepari, wholesaler, retailer (urban) and retailer (rural) were 430.00, 691.00, 2184.00, 2443.00, 1857.00 and 1074.00 Tk ton-1, respectively. Net margin or profit of the faria, bepari, wholesaler and retailer were 1300.00, 817.00, 557.00 and 2143.00 Tk ton-1, respectively. There were seven marketing channel exist in tomato marketing. Total marketing cost of all intermediaries was 7604.00 Tk ton-1 and net margin was 4826.00 Tk ton-1. Marketing efficiency was 2.25. Price spread between consumer paid and producer received was 8000.00 Tk ton-1. On the other hand, producer share was 78 percent. Spoilage and damage, transportation and packaging were the main marketing problem of summer tomato. Int. J. Agril. Res. Innov. Tech. 12(1): 12-17, June 2022